2015
DOI: 10.1149/06917.1017ecst
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hygrothermal Ageing on PFSA Ionomers' Structure/Property Relationship

Abstract: Perfluorosulfonic-acid (PFSA) membranes are frequently subjected to high humidity and temperature cycles during fuel-cell operation. It is of great interest to understand how the properties of the membrane change with ageing conditions and time. In this study, we investigate how the properties of as-received and pretreated Nafion membranes change after exposure to hygrothermal ageing, including the chemical structure, mechanical properties, water uptake, ionic conductivity, and morphology. Our findings demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“… However, unlike thermal annealing, aging does not change crystallinity. , The SAXS data are consistent with this in that after aging the ionomer peak shifts significantly to the right and broadens, implying a wider distribution of smaller and maybe even isolated water domains. Also, the d w –λ trend (discussed in section ) shifts downward upon aging ( d w decreases more than λ) indicating a break in the hydration vs d -spacing correlation (Figure ), where the aging-induced cross-links prevent expansion and perhaps connectivity of the water domains. ,,,, This is consistent with the more severe decrease in ionic conductivity than can be solely explained by changes in EW and water uptake as observed by Collette et al and Clapham et al, who reported a conductivity loss of 80% versus a 49% increase in EW.…”
Section: Other Topicssupporting
confidence: 71%
See 4 more Smart Citations
“… However, unlike thermal annealing, aging does not change crystallinity. , The SAXS data are consistent with this in that after aging the ionomer peak shifts significantly to the right and broadens, implying a wider distribution of smaller and maybe even isolated water domains. Also, the d w –λ trend (discussed in section ) shifts downward upon aging ( d w decreases more than λ) indicating a break in the hydration vs d -spacing correlation (Figure ), where the aging-induced cross-links prevent expansion and perhaps connectivity of the water domains. ,,,, This is consistent with the more severe decrease in ionic conductivity than can be solely explained by changes in EW and water uptake as observed by Collette et al and Clapham et al, who reported a conductivity loss of 80% versus a 49% increase in EW.…”
Section: Other Topicssupporting
confidence: 71%
“…Since the early SAXS works by Roche et al, , Gierke and co-workers, , and Fujimura et al , reported a humidity-dependent ionomer peak associated with a phase-separated nanostructure, a large number of studies have employed SAXS/SANS to delineate PFSA morphological features. Such investigations include the effect of hydration, ,,,,,,,,,,,,,− ,,,,, temperature and thermal history, ,,,,,,,,,, freeze, , aging, ,, mechanical loads, stretching and orientation, ,,,,,,,,,,, time, ,, cations, ,,,, solvents, ,,, and PFSAs in dispersion state. , Early studies employed thermodynamics-based models to predict the hydrophilic domain formation in the hydrophobic matrix based on an energy balance between the electrostatic interactions and deformation of the surrounding matrix as mentioned in section . ,,,…”
Section: Morphological Featuresmentioning
confidence: 99%
See 3 more Smart Citations